Does the reduction in obstetric hospitals result in an unintended decreased in-hospital delivery utilisation? A causal multilevel analysis in China - Jay Pan; Nan Chen; Peter C Coyte (BMJ Public Health)
Introduction China’s progress towards achieving Sustainable Development Goals for maternal health is largely attributed to a reduction in maternal mortality rates, driven by increased in-hospital delivery services utilisation. However, recent reductions in the number of obstetric hospitals have raised concerns about compromised access to these services. This study investigates the impact of reduced obstetric hospitals on spatial accessibility and the utilisation of in-hospital delivery services.Methods Data from 2016 to 2020 were collected from a densely populated province with approximately 83 million residents. Directed Acyclic Graph was applied to identify a minimally sufficient set of confounders, including residential characteristics and transportation-related factors. Multilevel regression models were employed to analyse the causal effects, with sensitivity analysis using fixed effect and quantile regression models.Results Between 2017 and 2020, the number of obstetric hospitals decreased by 21.3% (from 1209 to 951), leading to a decline in the proportion of pregnant women covered within a 2-hour driving radius (from 97.4% to 97.1%) and an increase in the maximum of shortest driving time within county (from 117.2 to 121.0 min). Multilevel regression models, adjusted for confounders, showed that a 1 percentage point increase in the proportion of pregnant women covered within a 2-hour driving radius was associated with a 13 percentage point (95% CI: 11.4 to 14.7) increase in in-hospital delivery rates, especially in areas with lower coverage and in-hospital delivery rates.Conclusions The reduction in obstetric hospitals increased travel distances, negatively impacting in-hospital delivery utilisation. Expanding the proportion of pregnant women covered within a 2-hour driving radius may be more effective than reducing the maximum of shortest travel distance within a county when optimising obstetric hospital locations. These findings provide insights for optimising obstetric facility locations in similar low- and middle-income countries. While improving spatial accessibility is important, the potential quality gains from centralising obstetric resources should also be considered.